Effects of welding parameters on friction stir spot welding of high density polyethylene sheets - BİLİCİ, MUSTAFA KEMAL (ELSEVIER SCI LTD, 2012)
Friction stir spot welding parameters affect the weld strength of thermoplastics, such as high density polyethylene (HOPE) sheets. The effects of the welding parameters on static strength of friction stir spot welds of high density polyethylene sheets were investigated. For maximizing the weld strength, the selection of welding parameters is very important. In lap-shear tests two fracture modes were observed; cross nugget failure and pull nugget failure. The tool rotational speed, tool plunge depth and dwell time were determined to be important in the joint formation and its strength. The joint which had a better strength fails with a pull nugget failure morphology. Weld cross section image analysis of the joints were done with a video spectral comparator. The plunge rate of the tool was determined to have a negligible effect on friction stir spot welding. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: ALUMINUM-ALLOYS; STATIC STRENGTH; AUTOMOTIVE APPLICATIONS; TOOL GEOMETRY; RESISTANCE